Propuesta de un programa de formación de tutores para el desarrollo de habilidades tutoriales de los alumnos de la facultad de educación y ciencias de la comunicación de la unt - Cabrera Cipiran, Betty Margarita (2015)
This research called “Proposal for a tutor training program to develop skills tutorials the students of the Faculty of Education and Communication Sciences at UNT” was aimed to raise a comprehensive proposal of a tutor training program aimed at future teachers of educational institutions of the region at various levels of Basic Education, using the bibliographical, theoretical analysis and diagnosis the views of the students of the Faculty of Education and Communication Sciences of National University of Trujillo (UNT), who validated as specialists questionnaire from various departments of the same faculty, whom an interview was applied work was applied cabinet in two phases, allowing define, together with the author, the profile of the tutor, and the philosophical, psychological and pedagogical rationale underpinning the program. This proposal came to identify staffing needs, theoretical and applicative training students in the School of Education and Communication Sciences at UNT in relation to the development of tutorials skills as future educational counselors from your requirement and experiences lived in their practice and in their capacity as students. Personal development tutor, tutoring training in theory and educational guidance and technical training in developing plans and mentoring programs for: Considering the results of diagnosis developed a proposal for tutor training program that involves the following aspects were raised level on that form.